- #1

STEMucator

Homework Helper

- 2,075

- 140

##-1 = -1##

##\frac{1}{-1} = \frac{-1}{1}##

##\sqrt {\frac{1}{-1}} = \sqrt{\frac{-1}{1}}##

##\frac{\sqrt{1}}{\sqrt{-1}} = \frac{\sqrt{-1}}{\sqrt{1}}##

##\sqrt{1} \sqrt{1} = \sqrt{-1} \sqrt{-1}##

##(\sqrt{1})^2 = (\sqrt{-1})^2##

##1 = -1##

##\frac{1}{-1} = \frac{-1}{1}##

##\sqrt {\frac{1}{-1}} = \sqrt{\frac{-1}{1}}##

##\frac{\sqrt{1}}{\sqrt{-1}} = \frac{\sqrt{-1}}{\sqrt{1}}##

##\sqrt{1} \sqrt{1} = \sqrt{-1} \sqrt{-1}##

##(\sqrt{1})^2 = (\sqrt{-1})^2##

##1 = -1##

A little teaser I found.